THE DISTRIBUTION OF HEAVY METALS IN SEDIMENT OF JAKARTA BAY - Rochyatun, Endang; Rozak, A. (Marine Research in Indonesia, 2008)
A survey on heavy metal content in seawater and sediment was conducted in Jakarta Bay in May and October 2004. There is indication of significant presence of heavy metal in sediment. The contents of heavy metals in sediment at the western part of Jakarta Bay varied as follows: Pb = 10.67-35.19 ppm, Cd = 0.04-0.30 ppm, Cu = 7.41-74.70 ppm, Zn = 76.99-497.53 ppm and Ni = 4.58-18.75 ppm. At the central part of Jakarta Bay, they varied as Pb = 6.69-64.44 ppm, Cd = 0.01-0.442 ppm, Cu = 1.19-40.60 ppm, Zn = 53.87-275.68 ppm and Ni = 4.09-11.88 ppm and at the eastern of Jakarta Bay, Pb content varied between 3.64 and 43.97 ppm, Cd = <0.001-0.320 ppm, Cu = 0.82-36.47 ppm, Zn = 78.27-230.68 ppm and Ni = 4.58-11.02 ppm. The concentration of Pb in May and of Cu in Octobei 2004 were found higher near the coast and decreases towards the open sea, which is commonly found in front of estuary such Angke and Cengkareng Drain. The concentration of Cd in Jakarta Bay was constant at all stations and does not show any correlation with the distance of station and estuary. Heavy metals content in sediment was high in Jakarta Bay.